New versus old: 95 degree angled blade plate versus distal femoral locking plate. A randomized clinical trial. Issue 6 (June 2021) - Patterson, Brendan M.; Breslin, Mary A.; Wadenpfuhl, Leanne K.; Vallier, Heather A.
Highlights: Randomized comparison of 95 angled blade plate (ABP) versus distal femoral locking plate (LCP) did not support LCP to have superior performance in treatment of fractures amenable to either implant. Three patients developed nonunion after LCP versus none after ABP. Eight patients had a secondary unplanned procedure after LCP versus two after ABP. Abstract: Introduction: The purpose was to compare the locking condylar plate (LCP) with the 95° angled blade plate (ABP) for distal femoral fracture patterns amenable to either device. Our hypothesis was that LCP would outperform ABP with primary outcome of nonunion and secondary outcomes of reoperation and malunion. Methods: 78 adult patients with 79 eligible fractures and mean age of 60 years were prospectively randomized to LCP (n = 45) or ABP (n = 34). Mean ISS was 16. 22% fractures were open. Patient-reported functional outcomes were assessed with the Musculoskeletal Function Assessment (MFA). Results: All patients were followed to union, and mean follow-up was 25 months. There were no differences in age, sex, fracture pattern, co-morbidities or mechanism for the two groups. Three patients had infections, one superficial after LCP and one deep infection each after ABP and LCP. Three patients developed nonunion after LCP versus none after ABP (p = 0.06). Nine patients healed with minor deformity after LCP versus 5 following ABP. One fracture had major deformity after ABP versus two after LCP. Eight patients had a secondary procedure following LCP versus two after ABP (p = 0.05). Conclusions: The investigation failed to support newer technology being better. Evidence did not indicate the LCP was superior to the ABP. Trends for primary union and fewer secondary procedures suggest that ABP may have superior performance to LCP for fracture patterns which may be treated with either implant.